The prophets agree: the function of the book of the Twelve Prophets in Acts - White, Aaron W. ca. 21. Jh. (Biblical interpretation series, 2020)
Intro -- Contents -- Acknowledgments -- Abbreviations -- Introduction A Case for a Study on the LXX-Twelve Prophets in Acts -- I Flourishing Bones: an Introduction to a Study of the LXX-Twelve Prophets in Acts -- I.a The Twelve Prophets and Their Presence in the NT -- I.b The Twelve Prophets in Acts: a Case for Closer Analysis -- II Previous Work on the TP in Acts and Models of Interpretation -- II.a "The Exegetes" -- II.b The "Conversationalists" -- II.c Summary -- III A New Study on the TP in Acts -- III.a A Dialogue about the Twelve Prophets among Readers -- III.b Setting the Stage for the Lukan Use of the Twelve Prophets -- III.c The Process of Hearing Each Voice and Its Interaction with the Others -- IV The Argument and the Direction of the Study -- Chapter 1 "I Will Pour out My Spirit": Jesus the Lord and the Lukan Reading of LXX-Joel 3:1-5 in Acts 2 -- The Text of LXX-Joel 3:1-5 and of Acts 2:17-21 -- I Introduction -- II "I Will Pour out My Spirit": LXX-Joel 3:1-5 -- III LXX-Joel 3:1-5 in Acts 2: God's Attestation of the Lord and His Witnesses -- III.a The Case of Three Witnesses -- III.b Lukan Amendments to LXX-Joel 3:1-5 -- III.c Luke's Case for Jesus as Lord of the Day of the Lord by Three Witnesses -- III.d Summary -- IV Joel 3:1-5 in The Testament of Judah 24 -- IV.a An Opening Note on the Context and Its Problems Regarding The Testament of Judah -- IV.b A Future Age of Restoration: "After These Things …" -- IV.c The Outpouring of the Spirit upon the Sons of Truth -- IV.d Salvation: "Call upon the Name of the Lord" -- IV.e Summary -- V Luke and The Testament of Judah 24: a Conversation among Readers -- Chapter 2 "Forty Years": the Divided People of God and the Lukan Reading of LXX-Amos 5:25-27 in Acts 7:42-43 -- The Text of LXX-Amos 5:25-27 and of Acts 7:42-43 -- I Introduction.